ESTRATÉGIAS PARA MINIMIZAR OS RISCOS ERGONÔMICOS EM TRABALHADORES DE LIMPEZA: REVISÃO INTEGRATIVA - Emanuelli Mancio Ferreira da Luz; Oclaris Lopes Munhoz; Bruna Xavier Morais; Silvana Cruz da Silva; Franciele Ormizinda Almeida; Tânia Solange Bosi de Souza Magnago (Universidade Federal do Paraná, 2021)
Objective: to identify strategies to minimize ergonomic risks in the cleaning staff. Method: an integrative review, carried out on LILACS, Scopus, and MEDLINE/PUBMED databases, between August and September of 2019. The descriptors "ergonomics", "cleaning service", and their synonyms were combined using Boolean operators. Results: from the 21 articles analyzed, intervention studies prevailed and were classified with a level of evidence 2 (52%); carried out in the year 2012 (33.3%), in Sweden (38%), with hospital cleaning staff (47.6%). The use of ergonomic education strategies, changes in work tools, aerobic exercise, a method for risk assessment, surveillance protocol, task diary, updating with organizational and psychosocial factors at work were evidenced. Conclusion: the evidenced strategies proved to be effective and may contribute, for the health area, in the promotion and recovery of the physical condition of the cleaning staff.